Building Students’ Confidence in Speaking English through Differentiated Instruction - Rika Sandi Arianto; Juhana Juhana; Ruminda Ruminda (Lectura : Jurnal Pendidikan, 2023)
Differentiated Instruction is a way of learning where teachers make adjustments in content, process, product, and learning environment to improve students’ learning ability. This research aims to explore how English teachers implement Differentiated Instruction and build students’ confidence in speaking English. This research was a case study. The informants were two English teachers of Sekolah Menengah Pertama Negeri (SMPN) 4 Jember, 31 students of class VIID, and 31 students of class VIIF. The data were collected through observation, interviews, and questionnaires. The data were analyzed using data condensation, data display, and conclusion drawing/verification. The results showed that the English teachers had implemented all elements of Differentiated Instruction to build students’ confidence in speaking English. In the interview, the teachers stated that they used various methods such as presentation, discussion, question and answer, and games to make students confident in speaking English. The interview results were in line with the observation results where during the implementation of Differentiated Instruction, teachers had provided various activities to encourage students to be more confident in speaking English. Based on the questionnaire results, there was an increasement in students’ confidence in speaking English during the implementation of Differentiated Instruction. The finding showed that the confidence of students in classes VIID and VIIF to speak English increased by 6.23% for class VIID and 1.72% for class VIIF. From the results of the study, it can be concluded that Differentiated Instruction can increase students’ confidence in speaking English.